Hydrothermal synthesis of hexagonal-phase NaYF4：Er,Yb with different shapes for application as photovoltaic up-converters - 王东丰 张晓丹 刘永娟 吴春亚 张存善 魏长春 赵颖 (中国物理B：英文版, 2013)
Hexagonal β-NaYF4 co-doped with Yb3＋ and Er3＋ is directly synthesized under mild conditions using a hydrothermal method.The variation of the ratio of Ln3＋ to F-and ethylenediaminetetraacetic acid（EDTA） causes the shape of the microcrystal to change from microplate to microcolumn.The NaYF4 powder is mixed with polydimethylsiloxane（PDMS） to create an up-converter for thin film amorphous silicon solar cells so as to evaluate the effectiveness of the synthesized material as an up-converter.In order to overcome the difficulty in measuring the effectiveness of up-conversion material,a new method of using near infrared illumination to measure the short circuit current densities of solar cells both with and without up-converters is developed.An up-converter with pure hexagonal NaYF4：Yb3＋/Er3＋ microcrystal produces a high current output.Emission intensity data obtained by photoluminescence suggest that pure hexagonal NaYF4：Yb3＋/Er3＋ microcrystals are more efficient than nanocrystals when used as up-converting phosphors.